2015
DOI: 10.1002/lsm.22440
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of cryolipolysis for non‐invasive reduction of submental fat

Abstract: Background and ObjectivesCryolipolysis has previously received FDA clearance for fat reduction in the abdomen, flanks, and thighs. There is also interest in small volume fat reduction for areas such as the chin, knees, and axilla. This article reports the results of a cryolipolysis pivotal IDE study for reduction of submental fullness.Study Design/Material and MethodsA prototype small volume vacuum applicator (CoolMini applicator, CoolSculpting System, ZELTIQ Aesthetics) was used to treat 60 subjects in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 17 publications
(31 reference statements)
6
106
2
Order By: Relevance
“…The efficacy of this bilateral submental cryolipolysis procedure was similar to that found in the prior study of central submental cryolipolysis 16 since fat layer reduction was mea- mental treatment study, skinfold caliper data demonstrated a mean (SD) fat layer reduction of 2.3 (0.8) mm. The mean (SD) fat thickness reduction measured via 3-D imaging was 3.77 (3.59) mm in the central submental area.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The efficacy of this bilateral submental cryolipolysis procedure was similar to that found in the prior study of central submental cryolipolysis 16 since fat layer reduction was mea- mental treatment study, skinfold caliper data demonstrated a mean (SD) fat layer reduction of 2.3 (0.8) mm. The mean (SD) fat thickness reduction measured via 3-D imaging was 3.77 (3.59) mm in the central submental area.…”
Section: Discussionsupporting
confidence: 72%
“…These participant surveys show higher satisfaction than the previous central submental study, which determined that 83% of participants were satisfied with submental cryolipolysis and 77% reported visible fat reduction. 16 The increased satisfaction in the present study may be a result of enhanced fat reduction since both the central and lateral portions of the submental area were treated, leading to more aesthetically pleasing chin and neck contouring, and to the fact that participants started with more submental fat than the participants in the previous study. However, the present study did not have a single-application control in the central submental area for direct comparison, and these survey results are being compared across studies.…”
Section: Discussionmentioning
confidence: 84%
“…However, the destruction of adipocytes does not affect serum lipid levels or liver function tests significantly. In spite of being a new technology without a fully understood mechanism of action, promising results have been confirmed in studies; therefore, it seems to be an excellent alternative for localized fat reduction without major adverse effects [79]. This case report was conducted in order to validate the effects of this therapy in eliminating abdominal fat cells, through histological and ultrasound examinations.…”
Section: Introductionmentioning
confidence: 99%
“…2, 7 Overall, reported side effects with ATX-101 in clinical trials were typically mild to moderate, transient, and localized to the injection site 4, 7, 10, 11. The most commonly reported events were minor and included pain, edema, erythema, and bruising; and notably, these events frequently occurred in the placebo groups as well 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13. This was not surprising because the aforementioned adverse events are the most common and expected effects associated with all injection-based procedures 3, 4, 11.…”
Section: Discussionmentioning
confidence: 97%